Pulmonary Syphilis: A Narrative Review - Kamil, Aulia; Medison, Irvan; Wahyu Fitrina, Dewi; Mizarti, Dessy (Syntax Corporation, 2026)
Pulmonary syphilis is a rare medical condition characterized by lung tissue involvement caused by infection with Treponema pallidum. According to the 2024 WHO report, approximately eight million men and women aged 15–49 years are infected with syphilis globally. Although uncommon, pulmonary involvement has been reported in 1%–12.5% of syphilis cases based on autopsy studies. The main risk factors include untreated syphilis, immunocompromised conditions, and co-infections. This study aims to describe the characteristics, diagnostic approach, and management of pulmonary syphilis to improve understanding of early detection and appropriate treatment. This study used a literature review approach by analyzing epidemiological data and previous studies discussing clinical, radiological, and laboratory findings in the diagnosis of pulmonary syphilis, as well as its therapeutic management. The findings indicate that the diagnosis of pulmonary syphilis requires a comprehensive approach, including clinical evaluation, radiological imaging of the lungs, and laboratory confirmation. Pharmacological management through antibiotic therapy remains the primary treatment to control infection and prevent disease progression. Pulmonary syphilis is a rare but potentially serious complication of syphilis infection. Early detection through comprehensive diagnostic evaluation and appropriate antibiotic treatment is essential to prevent complications and reduce the spread of infection.